Projeto professor conectado : implicações pedagógicas no trabalho docente - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
This dissertation research is linked to Education, School and Technology line and investigates the pedagogical implications of the laptop uses in the first years of elementary school teachers included in the project Teacher Connected, the Municipal Education Network Anapolis (GO). The survey was conducted in local schools and main goal was to investigate how teachers research subjects using the laptop in their teaching practices and until what level such technological tool is used to support the teaching- learning process. The theoretical foundation was anchored in Vygotskis basics of teaching- learning (learning) and the upcoming productions of authors of such concepts in their research on the use of technology in teaching. Developed a qualitative research, exploratory, using as instruments data collection classroom observation of teachers investigated and the application of a questionnaire. The study showed that the use of the laptop and other technological resources in the pedagogical practices of teachers was investigated predominantly utilitarian and pragmatic way, without incorporation into the pedagogical work, which allows us to infer the involvement of the mediation process of student learning. They met, however, no evidence of an early didactic dialogue to incorporate technological resources, in particular, laptop, professional and continuing education of teachers and the teaching- learning process, which points to an already open way. Empirical research data indicate that the subjects investigated have difficulty initially to realize another approach in the teaching-learning process than the technicalities, however, there are possibilities to transform this reality, if there is some investment in the continuing education of teachers.
Keywords: Tecnologia na educação; Notebook e ensino; Projeto Professor Conectado; Technology in education; Laptop and teaching; Connected Teacher Project; CIENCIAS HUMANAS::EDUCACAO